Aspek Pertanggungjawaban Hukum dalam Pengelolaan Dana Desa Berdasarkan Regulasi Desa - Abdul Hakim; Yogi Fuji Syamsuri; Bandi Saepudin; Rahayudin Rahayudin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Village Fund Management is an important instrument in realizing participatory, transparent, and sustainable village development. However, in the practice of managing village funds, various legal issues often arise, especially those related to the accountability of Village Apparatus in financial planning, implementation, and reporting. This article aims to analyze the Aspects of Legal Accountability in Village Fund Management Based on the Village Regulatory Framework, including Law Number 6 of 2014 concerning Villages, Government Regulation Number 43 of 2014 in conjunction with Government Regulation Number 47 of 2015, and the Regulation of the Minister of Villages, Disadvantaged Regions and Transmigration regarding village financial management. The approach used is normative juridical with a focus on the analysis of laws and regulations, the principles of state administrative law, and the concept of state financial accountability. The study results indicate that the legal accountability of village officials consists of administrative accountability, financial accountability, and criminal liability for irregularities or state losses. Weaknesses in apparatus capacity, minimal internal oversight, and inaccurate reporting documentation are the main factors causing these irregularities. This article emphasizes the importance of strengthening the legal capacity of village officials, optimizing a multi-level oversight system, and implementing accountability principles to achieve good, transparent, and violation-free Village Fund governance.